Tuning the magneto-optical response of TbPc2 single molecule magnets by the choice of the substrate1. Issue 31 (21st August 2015) - Robaschik, Peter; Fronk, Michael; Toader, Marius; Klyatskaya, Svetlana; Ganss, Fabian; Siles, Pablo F.; Schmidt, Oliver G.; Albrecht, Manfred; Hietschold, Michael; Ruben, Mario; Zahn, Dietrich R. T.; Salvan, Georgeta
<x xml:space="preserve">Abstract</x> Magneto-optical Kerr rotation of thin films of TbPc2 single molecule magnets can be tuned at room temperature within almost two orders of magnitude by the choice of the substrate.